Potential role of microRNAs in selective hepatic insulin resistance: From paradox to the paradigm - Palihaderu, Palihaderu Arachchige Dineth Supasan; Mendis, Balapuwaduge Isuru Layan Madusanka; Premarathne, Jayasekara Mudiyanselage Krishanthi Jayarukshi Kumari; Dias, Wajjakkara Kankanamlage Ruwin Rangeeth; Yeap, Swee Keong; Ho, Wan Yong; Dissanayake, Arosha Sampath; Rajapakse, Iyanthimala Harshini; Karunanayake, Panduka; Senarath, Upul; Satharasinghe, Dilan Amila (Frontiers in Endocrinology, 2022)
The paradoxical action of insulin on hepatic glucose metabolism and lipid metabolism in the insulin-resistant state has been of much research interest in recent years. Generally, insulin resistance would promote hepatic gluconeogenesis and demote hepatic de novo lipogenesis. The underlying major drivers of these mechanisms were insulin-dependent, via FOXO1-mediated gluconeogenesis and SREBP1c-mediated lipogenesis. However, insulin-resistant mice models have shown high glucose levels as well as excess lipid accumulation. As suggested, the inert insulin resistance causes the activation of the FOXO1- pathway promoting gluconeogenesis. But it does not affect the SREBP1c- pathway therefore cells continue the de novo lipogenesis. Many hypotheses were suggested for this paradoxical action occurring in insulin-resistant rodent models. A “downstream branch point” in the insulin-mediated pathway was suggested to act differentially on the FOXO1 and SREBP1c pathways. MicroRNAs have been widely studied for their action of pathway mediation via suppressing the intermediate protein expressions. Many in-vitro studies have postulated the roles of hepato-specific expressions of miRNAs on insulin cascade. Thus, miRNA would play a pivotal role in selective hepatic insulin resistance. As observed, there were confirmations and contradictions between the outcomes of gene knock-out studies conducted on selective hepatic insulin resistance and hepato-specific miRNA expression studies. Further, these studies had evaluated only the effect of miRNAs on glucose metabolism and few on hepatic de novo lipogenesis, limiting the ability to conclude their role in selective hepatic insulin resistance. Future studies conducted on the role of miRNAs on selective hepatic insulin resistance warrant the understanding of this paradoxical action of insulin.